2015
DOI: 10.3391/ai.2015.10.1.08
|View full text |Cite
|
Sign up to set email alerts
|

Parasite host-switching from the invasive American red-eared slider, Trachemys scripta elegans, to the native Mediterranean pond turtle, Mauremys leprosa, in natural environments

Abstract: This review examines the ecological, economical, and public health significance of chironomids and provides examples of chironomid invasions via international shipping and the subsequent local and regional impacts. Dispersal and adaptation mechanisms as facilitators of chironomid invasions are presented, and control methods are discussed. Impacts ranged from increased nuisance occurrences to agricultural disruption. Anthropogenic activities including pollution-related decimation of aquatic benthic communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…Furthermore, in a changing world where animals are sold for pets, some species may invade new environments and bring with them a great number of parasite species. Concerning turtles, Meyer et al [ 25 ] and Héritier et al [ 23 ] investigated the polystome richness among two European freshwater turtles, Mauremys leprosa (Schweigger, 1812) and Emys orbicularis (Linnaeus, 1758), respectively. They documented a greater polystome diversity than expected assuming a high degree of host- and site-specificity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in a changing world where animals are sold for pets, some species may invade new environments and bring with them a great number of parasite species. Concerning turtles, Meyer et al [ 25 ] and Héritier et al [ 23 ] investigated the polystome richness among two European freshwater turtles, Mauremys leprosa (Schweigger, 1812) and Emys orbicularis (Linnaeus, 1758), respectively. They documented a greater polystome diversity than expected assuming a high degree of host- and site-specificity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a few polystome species reported within populations of M. leprosa and E. orbicularis were also found in American hosts that had never been recorded in the European freshwater environments of investigation. Meyer et al [ 25 ] and Héritier et al [ 23 ] showed that these parasite species were in fact introduced into natural wetlands following the introduction of the American red-eared slider T. s. elegans . Because that turtle is among the most common exotic turtle species in captivity, it would act as a reservoir of numerous parasite species [ 24 ], and, once released into freshwater habitats, it would have served as a carrier of parasites, as for instance Neopolystoma sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have colonized discrete ecological niches within the host, i.e. the urinary bladder, the pharyngeal cavity and the conjunctival sacs (Table 1), and are highly host and site specific, except when turtles are translocated in new environments (see Meyer et al, 2015;Verneau et al, 2011). Regarding our phylogeny that comprises 20 species collected from 16 distinct turtles (Fig.…”
Section: Origin and Evolution Of Chelonian Polystomesmentioning
confidence: 99%
“…and snails in Bermuda [84]. Finally, red-eared sliders may transmit parasites to native chelonians [85,86].…”
Section: Communitiesmentioning
confidence: 99%